Multiplex ligation-dependent probe amplification identifies copy number changes in normal and undetectable karyotype MDS patients - Ma, Jing; Ai, Xiaofei; Wang, Jinhuan; Xing, Limin; Tian, Chen; Yang, Hongliang; Yu, Yong; Zhao, Haifeng; Wang, Xiaofang; Zhao, Zhigang; Wang, Yafei; Cao, Zeng (Annals of hematology, 2021)
Chromosomal abnormalities play an important role in classification and prognostication of myelodysplastic syndrome (MDS) patients. However, more than 50% of low-risk MDS patients harbor a normal karyotype. Recently, multiplex ligation-dependent probe amplification (MLPA) has emerged as an effective and robust method for the detection of cytogenetic aberrations in MDS patients. To characterize the subset of MDS with normal karyotype or failed chromosome banding analysis, we analyzed 144 patient samples with normal karyotype or undetectable through regular chromosome banding analysis, which were subjected to parallel comparison via fluorescence in situ hybridization (FISH) and MLPA. MLPA identifies copy number changes in 16.7% of 144 MDS patients, and we observed a significant difference in overall survival (OS) (median OS: undefined vs 27 months, p=0.0071) in patients with normal karyotype proved by MLPA versus aberrant karyotype cohort as determined by MLPA. Interestingly, patients with undetectable karyotype via regular chromosome banding indicated inferior outcome. Collectively, MDS patients with normal or undetectable karyotype via chromosome banding analysis can be further clarified by MLPA, providing more prognostic information that benefit for individualized therapy.